Editorial Foreword - Milnacipran: recent findings in depression - Stuart Montgomery (Dove Medical Press, 2010)
Stuart Montgomery1, Mike Briley2 1Imperial College School of Medicine, London, England, UK; 2NeuroBiz Consulting and Communication, Castres, FranceMilnacipran: recent findings in depressionMilnacipran is a serotonin and norepinephrine reuptake inhibitor (SNRI) which was first approved for the treatment of major depressive episodes in France in December 1996. It is currently marketed for this indication (as Ixel®, Toledomin®, Tivanyl® or Dalcipran®) in over 45 countries worldwide including Japan. It was approved for the management of fibromyalgia in the US in 2009.This supplement, which is based on a symposium at the International Forum on Mood and Anxiety (IFMAD) held in Monaco in November 2009, highlights several recent clinical studies with milnacipran in depression.